2014
DOI: 10.1364/ol.39.001235
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-coated microfiber Bragg grating for high-sensitivity gas sensing

Abstract: A graphene coated microfiber Bragg grating (GMFBG) for gas sensing is reported in this Letter. Taking advantage of the surface field enhancement and gas absorption of a GMFBG, we demonstrate an ultrasensitive approach to detect the concentration of chemical gas. The obtained sensitivities are 0.2 and 0.5 ppm for NH3 and xylene gas, respectively, which are tens of times higher than that of a GMFBG without graphene for tiny gas concentration change detection. Experimental results indicate that the GMFBG-based NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(84 citation statements)
references
References 16 publications
0
84
0
Order By: Relevance
“…Deposition of graphene and its derivatives on fiber surface could enhance the performance of optical fiber devices (Wu et al, 2014;Sridevi et al, 2016). However, the lack of efficient transfer techniques limited the usage of graphene and GO for fiber device with cylindrical shape and small diameter.…”
Section: Functionalization Of Go-dlpg Sensormentioning
confidence: 99%
“…Deposition of graphene and its derivatives on fiber surface could enhance the performance of optical fiber devices (Wu et al, 2014;Sridevi et al, 2016). However, the lack of efficient transfer techniques limited the usage of graphene and GO for fiber device with cylindrical shape and small diameter.…”
Section: Functionalization Of Go-dlpg Sensormentioning
confidence: 99%
“…Meanwhile, it has been shown that the graphene layer can be tightly coated onto a nanowire due to van der Waals forces [16][17][18]. Sketched in Fig.…”
Section: The Plasmons Resonator Based On Graphene-coated Insb Nanowirementioning
confidence: 99%
“…Thus alternative approaches for enhancing SRI sensitivity constantly pursued. As such, coating of graphene (oxide) or carbon nanotubes (CNTs) on the etched FBG surface to redistribute the evanescent field were used for gas or bio-sensing with high sensitivity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%